Pengruh Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Badan Perencanaan Pembangunan Daerah Kabupaten Kolaka Utara - Asrul, Alfia; Muhammadiah, Muhammadiah; Mustari, Nuryanti (Universitas Muhammadiyah Makassar, 2021)
ABSTRACTThis study aimed to describe and explain the influence of organizational culture on employee performance at the Regional Development Planning Agency Office of North Kolaka Regency. This research used quantitative. The sample in this study was 51 people with sampling technique using saturated sampling. The results showed that the organizational culture with the indicators was in the good category and the employee performance with the indicators also was in the good category. The results of this study used a simple regression analysis which showed that organizational culture was very influential on employee performance. This meant that the better the culture applied to the organization, the better the performance produced by the employees. Keywords: Influence, organizational culture, employee performance